Abroad - Crouch, Katie (Sarah Crichton Books, Farrar, Straus and Giroux, 2014)
The old Etruscan city of Grifonia swarms with year-abroad students; ostensibly, they've come to study. But really they are here to reinvent themselves, to shuck their identities and buck constraints far from the watchful eyes of parents and others who know them too well. Today's young ladies don't travel with chaperones... and Grifonia is a city filled with dangerous secrets of many kinds: ancient, eternal, infernal....